Women’s Promotion to Managerial Positions in Iranian Organizations: A Systematic Review Approach - Sadeghpour Dilmaghani , Mahsa; Gholipour , Arian; Roshandel Arbatani, Taher; Mohammadesmaeili, Neda (Management Strategies and Engineering Sciences, 2024)
This study aims to explore the key factors Impacting the promotion of Iranian women to managerial positions in Iranian organizations. By identifying barriers and facilitators across individual, social, cultural, and organizational domains, this research seeks to provide a comprehensive understanding of the challenges women face in ascending to leadership roles and offer practical solutions to address these issues. The study employed a systematic review approach, analyzing existing literature and qualitative data from various academic sources. The research focused on identifying relevant themes through conceptual and axial coding. Articles were selected based on their focus on women’s promotion, gender roles, organizational culture, and leadership dynamics. A thematic analysis was conducted to extract key patterns related to women’s career progression, with particular attention to cultural and organizational barriers in Iran. The study identified several significant barriers to women’s promotion, including entrenched gender stereotypes, organizational cultures favoring male leadership, and the persistent glass ceiling effect. Work-family conflict also emerged as a critical impediment to women’s career growth. However, social support systems such as mentorship and organizational changes promoting diversity were found to be facilitators of promotion. Personal traits such as perseverance and assertiveness also contributed to overcoming these barriers, though broader cultural and organizational support remains essential for sustained progress. While there has been some progress in the promotion of women to managerial positions in Iranian organizations, substantial barriers persist. Gender stereotypes, organizational culture, and work-family conflict continue to limit women’s career opportunities. To foster women’s promotion, organizations must implement supportive policies, mentorship programs, and cultural shifts that promote gender equality and recognize diverse leadership styles.